Educating the Public Health Workforce: A Scoping Review - Tao, Donghua; Evashwick, Connie J.; Grivna, Michal; Harrison, Roger (Frontiers in Public Health, 2018)
The aim of this scoping review was to identify and characterize the recent literature pertaining to the education of the public health workforce worldwide. The importance of preparing a public health workforce with sufficient capacity and appropriate capabilities has been recognized by major organizations around the globe. No single repository offers a comprehensive compilation of who is teaching public health, to whom, and for what end. By examining the peer-reviewed literature, published primarily by academicians involved in educating those who will perform public health functions, this study sought to describe contemporary approaches to educating the public health workforce. The literature in the English language published between 2000 and 2015 was searched in three databases: Scopus, PubMed, and ERIC. An initial total of 1860 articles were reviewed for their relevancy by the four authors. The final total of articles deemed relevant for the study was 350. These articles were examined for distribution by year of publication, geography location of subject matter or first author, discipline, article type, and research methodology. Definitions, coding classifications, and procedures were carried out according to standard recommended processes. The results found articles published in all years and a wide range of geographic areas, including 46 specific countries. Health professions disciplines represented included medicine, nursing, dentistry, veterinary medicine, social work, pharmacy, physical therapy, public health in general, and eight sub-specialties within public health. Curriculum, instruction, and pedagogy was the most common classification of article type, representing more than 36% of the articles, with only about 10% of the articles employing original research methodologies. The 350 articles were written by 2432 authors, with no single center or university standing out as a leader in the field of public health workforce pedagogy. This scoping review identified a relatively small but robust array of articles by educators and practitioners engaged in educating the workforce that provides the essential functions of public health. Using published literature to share basic knowledge lays the groundwork for the systems approach to training a workforce that will be capable of performing essential public health functions within and across nations.